On the Psychology of TikTok Use: A First Glimpse From Empirical Findings - Montag, Christian; Yang, Haibo; Elhai, Jon D. (Frontiers in Public Health, 2021)
TikTok (in Chinese: DouYin; formerly known as musical.ly) currently represents one of the most successful Chinese social media applications in the world. Since its founding in September 2016, TikTok has seen wide-spread distribution, in particular attracting young users to engage in viewing, creating and commenting on “Lipsync-Videos” on the app. Despite its success in terms of user numbers, psychological studies aiming at an understanding TikTok use are scarce. This narrative review provides a comprehensive overview on the small empirical literature available thus far. In particular, insights from uses and gratification theory in the realm of TikTok are highlighted, and we also discuss aspects of the TikTok platform design. Given the many unexplored research questions related to TikTok use, it is high time to strengthen research efforts to better understand TikTok use and whether certain aspects of its use result in detrimental behavioral effects. In light of user characteristics of the TikTok platform this research is highly relevant, because TikTok users are often adolescents and therefore from a group of potentially vulnerable individuals.